NATO's new Strategic Concept: A comprehensive assessment - Jens Ringsmose; Sten Rynning (Danish Institute for International Studies (DIIS), 2011)
NATO agreed its new Strategic Concept at the Lisbon Summit in November 2010. The new Strategic Concept is analyzed in a DIIS Report edited by Jens Ringsmose and Sten Rynning. The report entitled NATO's New Strategic Concept: A Comprehensive Assessment contains 15 individual chapters all on different aspects of NATO's new Strategic Concept making the publication the first major and comprehensive analysis of the implications of NATO's new Strategic Concept. The publication is the outcome of cooperation between DIIS and University of Southern Denmark and draws on the contributions from a conference held in the immediate aftermath of the Lisbon Summit. The publication contains contributions from Danish scholars and practitioners as well as from a number of international NATO experts such as Klaus Wittmann, Mark Webber, Jamie Shea, Karl-Heinz Kamp, Adrian Hyde-Price, Paal Sigurd Hilde, Theo Farrell and Sven Biscop.
Keywords: 300; Bündnissystem; Militärpolitik